PENGARUH KEBIJAKAN BANK INDONESIA TENTANG PEMBATASAN KEPEMILIKAN KARTU KREDIT TERHADAP PERTUMBUHAN KARTU KREDIT DAN KARTU KREDIT MACET BERDASARKAN KELOMPOK BANK - Deara Shinta Lestari (Fakultas Ekonomi Universitas Bangka Belitung, 2020)
The aim of this research is to examine the impact of PBI SEBI 14/27/DASP/2012 in Indonesia. The examination is using Panel Data Regression Methods and Different Test of Independent Samples Test. The purposes are to compare the compare the effect of the growth of credit cards before and after the implementation of PBI SEBI 14/27 / DASP / 2012. The research period was from year 2008 to year 2015. The sample populations used are four groups based on ownership of banks are: State Owned Banks, Foreign Exchange Commercial Banks, Foreign Owned Banks and Joint Venture Banks and PT Bank Bukopin Tbk in each period. The result of this research shows that PBI SEBI 14/27/DASP/2012 has significant impact on revenue growth of credit cards and a decrease in the credit card NPL by a group of banks, and the growth of credit cards at PT Bank Bukopin has a significant influence on the growth of cards credit Quantity, the credit card NPL and Annual Fee credit card.